Peran Asuransi Syariah dalam Menyediakan Perlindungan Finansial yang Islami - Siregar, Abed Nego; Endang, Endang; Nababan, Fera Daniaty; Sianturi, Putri Titin; Ramli, Rafli; Tobing, Samuel (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
This study investigates the development and impact of sharia insurance in Indonesia, the country with the largest Muslim population in the world. The Islamic financial market in Indonesia has great potential because the majority of the population is Muslim. This study analyzes publications and journals in Indonesia that discuss sharia insurance using the literature review method. The research results show that sharia insurance has developed into a contemporary financial company that is able to compete with conventional insurance. Based on the main principles of Islam, such as Aqidah, Al Itu, Prophethood, Khilafah, and Ma'ad, sharia insurance includes products such as life insurance, education insurance, and health insurance. The sharia life insurance business uses tabarru' and mudharabah contracts to manage participant funds, which are invested in accordance with Sharia law. The concept, legal sources, sharia supervision, agreements, ownership and management of funds, premiums, and sources of payment for sharia insurance claims are different from conventional insurance. Through mutual cooperation, investment, and providing financial needs when risks occur, sharia insurance helps build a sustainable sharia economy. However, the economic crisis, capital needs, competition in regional markets, shortage of human resources, lack of public awareness, and product distribution problems are all the problems facing sharia insurance. Further efforts are needed to overcome difficulties and increase public understanding of the importance of sharia insurance.